PENGARUH JENIS PELARUT TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN ALPUKAT (Persea americana Mill) - Maranatha Cicilia; Wahyu Purwanjani; Gigih Kenanga Sari (Jurnal Farmasi IKIFA, 2024)
Avocado plant (Persea americana Mill) is one of the plants that have the benefit of preventing premature aging due to the antioxidant content. This study aims to determine the effect of solvent type ethanol 70%, ethyl acetate, n-hexane on antioxidant activity of avocado leaf extract (Persea americana Mill). The method used in this study was laboratory experimental, using 3 types of solvents in avocado leaf extract (Persea americana Mill) with several concentrations of 50 ppm, 100 ppm, 150 ppm, 200 ppm, and 250 ppm. Antioxidant activity of avocado leaves (Persea americana Mill) was conducted using the DPPH method, by analyzing the activity of free radical immersion in avocado leaf extract which was determined based on the value of IC50, then the data obtained were tested statistically. The results showed that the type of ethanol extract solvent has a very strong antioxidant activity with a value of IC50 24.69 ppm; the type of ethyl acetate extract solvent has a weak antioxidant activity with a value of IC50 172.84 ppm; and the solvent type of n-hexane extract has very weak antioxidant activity with IC50 value of 41.22 ppm. Different types of solvents affect the antioxidant activity of avocado leaf extract (Persea americana Mill).